Assessing the drivers of palm oil production in Malaysia: a quantile regression approach with environmental considerations - Duasa, Jarita; Idris, Zera Zuryana; Mohd Thas Thaker, Mohamed Asmy; Ahmad, Azlin Alisa (IOP Publishing, 2025)
This study examines the factors influencing palm oil production in Malaysia across different points of the output distribution, with a particular focus on environmental factors. Employing quantile regression, which provides a more comprehensive analysis than Ordinary Least Squares (OLS) by capturing heterogeneous effects across quantiles, we analyze time series data spanning from 1991 to 2022. The findings reveal that CO2 emissions significantly and positively contribute to palm oil production at lower quantile but become insignificant at higher quantiles. Pesticide use positively affects production at middle quantile, while labor has a consistently negative and significant impact across all quantiles. The results highlight the need for sustainable production practices, particularly for small-scale producers reliant on emissions-intensive methods. Stricter pesticide regulations and eco-friendly alternatives should be promoted to mitigate environmental risks. Additionally, addressing labor shortages through mechanization and workforce training is crucial for industry sustainability.